2021
DOI: 10.3389/fendo.2021.795627
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Endoscopic Thyroidectomy via a Chest-Breast Approach Has an Acceptable Safety Profile for Thyroid Nodule

Abstract: IntroductionWith the growing esthetic requirements, endoscopic thyroidectomy develops rapidly and is widely accepted by practitioners and patients to avoid the neck scar caused by open thyroidectomy. Although ambulatory open thyroidectomy is adopted by multiple medical centers, the safety and potential of ambulatory endoscopic thyroidectomy via a chest-breast approach (ETCBA) is poorly investigated.Material and MethodsPatients with thyroid nodules who received conventional or ambulatory ETCBA at Xiangya hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In our study, there was no significant difference in HAM-A scores between the two groups, indicating that patients in the ambulatory group were no more anxious than those in the conventional group. Zeyu-Zhang reported more anxiety among patients in the ambulatory group (30,31); this may be because we used multimedia to provide patients with a complete understanding of their condition and how to ensure their safety after discharge, thereby reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no significant difference in HAM-A scores between the two groups, indicating that patients in the ambulatory group were no more anxious than those in the conventional group. Zeyu-Zhang reported more anxiety among patients in the ambulatory group (30,31); this may be because we used multimedia to provide patients with a complete understanding of their condition and how to ensure their safety after discharge, thereby reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…There is no statistically significant difference in the incidence of postoperative hemorrhage between overnight thyroidectomy and inpatient thyroidectomy in terms of the incidence of postoperative hemorrhage ( 17 ). The difference in hypoparathyroidism in ECTBA was also not statistically significant ( 15 ). A prospective randomized controlled trial of 411 patients showed no difference in the incidence of complications such as hypoparathyroidism, hoarseness, hematoma, and wound infection between overnight and inpatient thyroidectomy ( 16 ).…”
Section: The Associated Complicationsmentioning
confidence: 97%
“…It is as safe as patients with benign thyroid nodules or thyroid cancer, with significant economic benefits and shorter hospital stays. Particular attention should be paid to the relief of anxiety and stress in patients receiving overnight ETCBA ( 15 ). The details of the two studies are shown in Table 1 .…”
Section: Progresses In Surgical Approachesmentioning
confidence: 99%
See 2 more Smart Citations